Preparation method and application of silicon dioxide aerogel

By using organosilicon ester and silica sol as the silicon source, combined with the gelation process and pH adjustment of the hydrolysate, the problems of high cost, low yield, low purity and poor thermal insulation performance in the prior art were solved, and SiO2 aerogel preparation with low cost, high purity and excellent thermal insulation performance were achieved.

CN119706855APending Publication Date: 2025-03-28ZHAOQING SANJIANG SILICON MATERIALS CO LTD
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202411914286.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-24
Publication Date
2025-03-28

AI Technical Summary

Technical Problem

In the prior art, the preparation of silica aerogels has problems such as high cost of silicon source, low yield, low purity and poor thermal insulation performance.

Method used

The silicone ester and silicon sol are used as the silicon source. Through the gelation process of the hydrolysate, the pH value is adjusted and the chelating agent is added to improve the purity and thermal insulation properties of SiO2 aerogel.

Benefits of technology

It reduces the preparation cost of SiO2 aerogel, improves yield and purity, and enhances thermal insulation performance, making SiO2 aerogel better perform in industrial applications.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119706855A_ABST
    Figure CN119706855A_ABST
Patent Text Reader

Abstract

The invention belongs to the technical field of silicon dioxide aerogel preparation, and discloses a silicon dioxide aerogel preparation method and application, the silicon dioxide aerogel preparation method comprises the following steps: S1, preparing a hydrolysate A; s2, gelatinizing the hydrolysate A; wherein S1 specifically comprises the steps that organic estersil is dissolved into a solution, the pH of the solution is adjusted to be acidic, then a chelating agent and silica sol are sequentially added, and hydrolysis is conducted to obtain hydrolysate A; according to the technology for preparing the silicon dioxide aerogel, on the basis that organic estersil is adopted, silica sol is jointly used as a silicon source for preparing the SiO2 aerogel, the technology for preparing the SiO2 aerogel can reduce the production cost by 6.4%-12.1%, the highest yield of the obtained SiO2 aerogel reaches 99%, the highest purity of the obtained SiO2 aerogel reaches 99.5%, the density of the obtained SiO2 aerogel is as low as 180 Kg / m < 3 >, the pore diameter of the obtained SiO2 aerogel is as small as 10-15 nm, and the porosity of the obtained SiO2 aerogel reaches 98%. The minimum heat conductivity coefficient is 0.0157 W / (m.K), and the heat insulation performance is excellent.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of silica aerogel preparation, and more specifically, to a silica aerogel preparation method and application. Background Art

[0002] Aerogel is a type of three-dimensional porous nano solid material, whose structure is formed by the interaction of colloidal particles or polymer molecules, with a porosity of 90% to 99.9%, a pore size of 1 to 100 nm, and the pores are filled with gaseous dispersion medium. Aerogel has the characteristics of ultra-lightness and nano-micropores. After a long period of development, many types of aerogel materials have been formed, such as oxide aerogel, organic aerogel, carbide aerogel, etc., but currently only silica aerogel can be industrialized on a large scale. Silica aerogel is a new type of inorganic nano thermal insulation material with the characteristics of low density, low thermal conductivity, high porosity, and large specific surface area. It has broad application prospects in thermal insulation, industrial catalysis, aerospace, pharmaceutical chemicals and other fields.

[0003] Regarding the preparation process of SiO2 aerogel, the prior art patent publication number: CN 103435055 A provides a method for preparing low-density silica aerogel under normal pressure, which discloses using tetraethyl orthosilicate as a silicon source, adding catalytic hydrolysis, hydrophobic modification, and drying to prepare SiO2 aerogel. The preparation method mainly has the following technical problems: (1) The silicon source for preparing SiO2 aerogel is all tetraethyl orthosilicate, which is an organic silicon, expensive, and has large fluctuations. The production capacity is greatly affected by the single crystal silicon industry; (2) The prepared SiO2 aerogel has low yield, low purity, and poor insulation performance. Summary of the invention

[0004] The invention provides a method for preparing SiO2 aerogel, which has low raw material cost and / or high purity of the prepared SiO2 aerogel.

[0005] Another object of the present invention is to provide application of the SiO2 aerogel in preparing thermal insulation materials.

[0006] In order to solve the above technical problems, the technical solution provided by the present invention is:

[0007] A method for preparing SiO2 aerogel, comprising:

[0008] S1. preparing hydrolyzate A;

[0009] S2. Gelation of hydrolyzate A;

[0010] S1. Specifically: dissolve the organic silicon ester into a solution, adjust the pH of the solution to be acidic, then add a chelating agent and silica sol in sequence, and hydrolyze to obtain a hydrolyzate A.

[0011] The present invention prepares SiO2 aerogel, and the principle of step S1 is shown in the following reaction formula ①:

[0012] ①Si(OR)4+4H2OSi(OH)4+4ROH

[0013] Reaction ① is a reversible reaction; wherein R represents an alkyl group.

[0014] The principle of step S2 is shown in the following reaction formula ②:

[0015] ②Si(OH)4→SiO2+2H2O

[0016] In the method for preparing SiO2 aerogel provided by the present invention, step S1 uses organic silicon ester and silica sol as a silicon source for preparing SiO2 aerogel, which plays the following roles:

[0017] 1. The cost of silica sol is about 1 / 5 of that of organic silicon ester. The addition of silica sol in the present invention can reduce the amount of organic silicon ester used and reduce the cost of preparing SiO2 aerogel.

[0018] 2. The SiO2 aerogel produced has high purity:

[0019] 1. Silica sol is used as an inducer to induce reaction ① forward reaction, which promotes Si(OR)4 in the organosilicon ester to generate Si(OH)4 hydrolysis solution A. The principle is as follows: the organosilicon ester is affected by the steric hindrance of the ethoxy group it contains, and it is difficult for it to be completely hydrolyzed and polycondensed by itself, so there are more free monomers gathered in the organosilicon ester solution; on the one hand, silica sol contains hydroxyl groups exposed on the surface, which can induce the hydrolysis and polycondensation of the organosilicon ester, and on the other hand, it contains silica particles, which act as "seeds" to accelerate the polycondensation of free monomers in the organosilicon ester solution, reduce the residual organic matter in the final SiO2 aerogel, and improve the purity of the SiO2 aerogel.

[0020] 2. Chelating agents can form complexes with Si(OH)4, promote the stability of Si(OH)4, and avoid the reverse reaction of reaction ①.

[0021] In addition, the skeleton pores formed by organic silicone esters are relatively large, while the silica sol molecules are nanometer-sized, which can "cut" the large pores, and the resulting aerogel has a small pore size (pore size distribution is between 5-30nm). Air molecules cannot move in the pores, so there is almost no heat transfer. Therefore, the resulting SiO2 aerogel has excellent thermal insulation properties.

[0022] Preferably, the mass ratio of organic silicon ester: silica sol: chelating agent in S1 is (80-200):(10-30):(0.5-2).

[0023] More preferably, the mass ratio of organic silicon ester: silica sol: chelating agent in S1 is (100-150): (15-25): (1-1.5).

[0024] The organic silicon ester of the present invention is selected from one or more of ethyl orthosilicate, methyl orthosilicate, polysilicate, methyltrimethoxysilane, methyltriethoxysilane and dimethyldimethoxysilane.

[0025] Preferably, in S1, the organosilicon ester is dissolved in alcohol to form a solution, and the pH is adjusted to 2-4.

[0026] Silica sol itself is a water system. Adding it to alcohol will destroy the hydration of silica sol and the double electric layer structure on the particle surface, resulting in the precipitation of silicon particles. In the present invention, when the pH of the system is adjusted to 2-4, the particle surface has a strong charge, the potential is increased, and the van der Waals force and electrostatic repulsion are in balance, ensuring that the silica sol remains stably dispersed in the alcohol.

[0027] The mass ratio of the organic silicone grease: alcohol: silica sol: chelating agent of the present invention is (80-200): (500-1000): (10-30): (0.5-2).

[0028] Preferably, the mass ratio of the organic silicone grease:alcohol:silica sol:chelating agent is (100-150):(600-800):(15-25):(1-1.5).

[0029] The alcohol described in the present invention is selected from one or more of ethanol, methanol, isopropanol and butanol.

[0030] The acid of the present invention is selected from one or more of hydrochloric acid, nitric acid, sulfuric acid, hydrofluoric acid, acetic acid and oxalic acid.

[0031] The chelating agent of the present invention is selected from one or more of ethyl acetoacetate, ethylenediaminetetraacetic acid, methylglycine diacetic acid and 1-3 diketone.

[0032] Chelating agents can slow down the direct condensation rate of monomers, chelate the monomers provided by silica sol, and make the pH of the organosilicon ester-silica sol system reach the target before condensation, so that the organosilicon ester and silica sol can fully react and the product structure is uniform. If the amount of chelating agent added is too little, the chelation strength is insufficient, and the silica sol monomers will condense and precipitate prematurely during the pH increase; if the amount of chelating agent added is too much, the gel time will be greatly extended, which is not conducive to production efficiency.

[0033] Preferably, the specific steps of gelling the hydrolyzate A in S2 are: adjusting the pH of the hydrolyzate A to be weakly alkaline to obtain sol B, and then subjecting it to aging, hydrophobic modification and drying to obtain SiO2 aerogel.

[0034] The aging method of the present invention is: putting sol B into a special mold, or with impregnated fiber felt, waiting for gelation to obtain wet gel or wet gel products, sealing and aging at room temperature for 8 to 16 hours.

[0035] The fiber felt described in the present invention is one of glass fiber felt, ceramic fiber felt, basalt fiber felt, pre-oxidized fiber felt, polyimide fiber felt and melamine foam.

[0036] Preferably, the pH of the hydrolyzate A in the gelling step S2 is 7-8.

[0037] Preferably, the hydrophobic modification process in S2 is to immerse the wet gel in a modifying liquid; the wet gel is obtained by aging sol B; the volume ratio of the wet gel to the modifying liquid is 1:(1-1.5); the modifying liquid is composed of a modifier and alcohol, wherein the content of the modifier in the modifying liquid is (3-15) wt%.

[0038] The modifier of the present invention is selected from one or more of hexamethyldisilazane, hexamethyldisiloxane, trimethylchlorosilane, dimethyldimethoxysilane and dimethyldiethoxysilane.

[0039] The wet gel in S2 of the present invention is immersed in the modifying liquid for 4 to 12 hours.

[0040] The alcohol in the modified solution of the present invention is consistent with the alcohol in step S1.

[0041] Preferably, the drying process in S2 is supercritical carbon dioxide drying; the pressure in the supercritical drying process is 16-20 MPa and the temperature is 50-70°C.

[0042] The specific method of supercritical carbon dioxide drying of the present invention is: the modified semi-finished material to be dried is placed in a drying kettle, the carbon dioxide is cooled into a liquid state, the pressure is increased to 16-20MPa by a high-pressure pump, and the temperature is heated to 50-70°C, and the supercritical state enters the drying kettle, the pressure of the drying kettle is increased to 16-20MPa, the temperature is increased to 50-70°C, and the temperature and pressure are maintained for 3-5 hours, and the gas-liquid separation is carried out in a separation kettle to obtain a SiO2 aerogel finished product.

[0043] Preferably, the S1 silica sol is one of commercially available alkaline silica sol, acidic silica sol and neutral silica sol, and the silicon dioxide content in the silica sol is ≥30wt%.

[0044] More preferably, the silicon dioxide content in the S1 silica sol is 40wt%, 50wt%.

[0045] The present invention calculates the amount of water required for the organic silicon ester reaction and the amount of silica sol required to be added, which corresponds to the water content in the silica sol, so as to control the amount of silica sol added to be consistent with the amount of water required by the reaction system. While providing a silicon source, it will not cause excessive water content in the system, and there is no need to change the liquid later, thereby simplifying the preparation process of SiO2 aerogel.

[0046] In the process of preparing SiO2 aerogel, alcohol is involved in the system circulation. Alcohol recycling is a conventional process. In the conventional preparation process in the prior art (without using silica sol), as the number of alcohol cycles increases, the impurity content becomes higher and higher, and the alcohol needs to be replaced every 3 to 6 months; and due to the high impurity content of the alcohol, a distillation tower is required to recover the alcohol. In the present invention, silica sol is added to the organic silicon ester as a silicon source. Since the silicon dioxide particles of the silica sol act as "seeds" to accelerate the condensation of the monomers, the organic monomer residues in the alcohol are reduced, which helps to stabilize the recycled alcohol. It only needs to be recovered by a simple evaporator, and the equipment investment and process costs are lower.

[0047] The present invention also provides the use of SiO2 aerogel prepared by any of the above-mentioned SiO2 aerogel preparation methods in the preparation of thermal insulation materials. BRIEF DESCRIPTION OF THE DRAWINGS

[0048] Figure 1 Process flow chart for preparing SiO2 aerogel for this application.

[0049] Figure 2 This is the microscopic morphology of the SiO2 aerogel obtained in Example 1.

[0050] Figure 3 This is the BET nitrogen adsorption-desorption diagram of the SiO2 aerogel obtained in Example 1.

[0051] Figure 4 This is a test diagram of the thermal conductivity of the SiO2 aerogel obtained in Example 1. DETAILED DESCRIPTION

[0052] The present invention is further described in detail below in conjunction with specific implementation methods.

[0053] Example 1

[0054] A method for preparing SiO2 aerogel comprises the following steps:

[0055] S1. The tetraethyl orthosilicate and ethanol were mixed and stirred at a speed of 500 rpm, a sulfuric acid solution was added to adjust the system pH to 3, ethyl acetoacetate and 30 wt% acidic silica sol were added in sequence, stirred evenly, sealed and allowed to stand for 6 hours to obtain a hydrolyzate A; the mass ratio of tetraethyl orthosilicate: alcohol: silica sol: ethyl acetoacetate was 110:665:22:1.2;

[0056] S2. The hydrolyzate A was added with an aqueous ammonia solution to adjust the pH of the hydrolyzate A to 7.5 to obtain a sol B;

[0057] S21. Aging process: Cut glass fiber needle felt of length*width*thickness (300*300*10mm), put it into a mold, impregnate sol B onto the fiber felt, seal it and let it stand until it is completely soaked, the gel time is 1h, and after gelation, let it stand and age for 10h to obtain a wet gel;

[0058] S22. Hydrophobic modification process: soaking the wet gel in a modification solution for 5 hours to obtain a modified semi-finished product; the modification solution is composed of trimethylchlorosilane and ethanol, wherein the content of trimethylchlorosilane in the modification solution is 3wt%; the volume ratio of the wet gel to the modification solution is 1:1.2;

[0059] S23. Supercritical carbon dioxide drying process: the modified semi-finished product is placed in a drying kettle; the liquid CO2 is pressurized to 18MPa by a high-pressure pump and heated to 65°C, and the CO2 enters the drying kettle in a supercritical state; when the pressure in the drying kettle rises to 17MPa and the temperature rises to 60°C, the temperature and pressure are maintained for 4 hours, and the gas and liquid are separated in a separation kettle to obtain the SiO2 aerogel product.

[0060] Example 2

[0061] This embodiment is the second embodiment of the present invention. The difference from the first embodiment is that the pH of the S1 regulating system is 2.

[0062] Example 3

[0063] This embodiment is the third embodiment of the present invention. The difference from the first embodiment is that the pH of the S1 regulating system is 4.

[0064] Example 4

[0065] This embodiment is the fourth embodiment of the present invention. Different from the embodiment 1, the mass ratio of tetraethyl orthosilicate:alcohol:silica sol:ethyl acetoacetate in S1 is 100:600:15:1.

[0066] Example 5

[0067] This embodiment is the fifth embodiment of the present invention. Different from the first embodiment, the mass ratio of tetraethyl orthosilicate:alcohol:silica sol:ethyl acetoacetate in S1 is 150:800:25:1.5.

[0068] Example 6

[0069] This embodiment is the fourth embodiment of the present invention. Different from the embodiment 1, the mass ratio of tetraethyl orthosilicate:alcohol:silica sol:ethyl acetoacetate in S1 is 80:500:10:0.5.

[0070] Example 7

[0071] This embodiment is the fifth embodiment of the present invention. Different from the embodiment 1, the mass ratio of tetraethyl orthosilicate:alcohol:silica sol:ethyl acetoacetate in S1 is 200:1000:30:2.

[0072] Example 8

[0073] This embodiment is the eighth embodiment of the present invention. The difference from the first embodiment is that S2 adjusts the pH of the hydrolyzate A to 7.

[0074] Example 9

[0075] This embodiment is the ninth embodiment of the present invention. The difference from the first embodiment is that S2 adjusts the pH of the hydrolyzate A to 8.

[0076] Example 10

[0077] This embodiment is the tenth embodiment of the present invention. Different from the first embodiment, in the S23 supercritical carbon dioxide drying process, the pressure of the drying kettle is increased to 16 MPa, the temperature is increased to 70°C, and the temperature and pressure are maintained for 5 hours.

[0078] Embodiment 11

[0079] This embodiment is the 11th embodiment of the present invention. Different from the embodiment 1, in the S23 supercritical carbon dioxide drying process, the pressure of the drying kettle is increased to 20 MPa, the temperature is increased to 50°C, and the temperature and pressure are maintained for 3 hours.

[0080] Example 12

[0081] This embodiment is the twelfth embodiment of the present invention. The difference from the first embodiment is that the organic silicon ester in S1 is polysilicate, the alcohol is methanol, the chelating agent is methylglycine diacetic acid, the silica sol is alkaline silica sol, and the sealed container is left to stand for 4 hours.

[0082] S21. The aging process is left to stand for 8 hours;

[0083] S22. The hydrophobic modification process is cyclically modified for 4 hours; the modification liquid is composed of hexamethyldisiloxane and methanol, wherein the hexamethyldisiloxane content in the modification liquid is 3wt%; the volume ratio of the wet gel and the modification liquid is 1:1.

[0084] Example 13

[0085] This embodiment is the twelfth embodiment of the present invention. The difference from the first embodiment is that the organic silicon ester in S1 is methyl orthosilicate, the alcohol is isopropyl alcohol, the chelating agent is ethylenediaminetetraacetic acid, the silica sol is neutral silica sol, and the mixture is sealed and left to stand for 12 hours.

[0086] S21. The aging process is left to stand for 16 hours;

[0087] S22. The modified gel was immersed for 12 hours in the hydrophobic modification process; the modification liquid consisted of trimethylchlorosilane and isopropanol, wherein the content of trimethylchlorosilane in the modification liquid was 15wt%; the volume ratio of the wet gel to the modification liquid was 1:1.5.

[0088] Comparative Example 1

[0089] This comparative example is the first comparative example of the present invention. Different from Example 1, the silicon source in S1 is only tetraethyl orthosilicate, and no silica sol is added. The mass ratio of tetraethyl orthosilicate: alcohol: ethyl acetoacetate is 132:665:1.2.

[0090] Comparative Example 2

[0091] This comparative example is the second comparative example of the present invention. Different from Example 1, no chelating agent is added to S1, and the mass ratio of tetraethyl orthosilicate: alcohol: silica sol is 110:665:22.

[0092] Comparative Example 3

[0093] This comparative example is the third comparative example of the present invention. Different from Example 1, S2 adjusts the pH of the hydrolyzate A to 6.

[0094] Comparative Example 4

[0095] This comparative example is the fourth comparative example of the present invention. Different from Example 1, the mass ratio of tetraethyl orthosilicate:alcohol:silica sol:ethyl acetoacetate in S1 is 70:480:9:0.3.

[0096] Comparative Example 5

[0097] This comparative example is the fourth comparative example of the present invention. Different from Example 1, the mass ratio of tetraethyl orthosilicate:alcohol:silica sol:ethyl acetoacetate in S1 is 210:1100:35:2.3.

[0098] Comparative Example 6

[0099] This comparative example is the sixth embodiment of the present invention. Different from the first embodiment, in the S23 supercritical carbon dioxide drying process, the pressure of the drying kettle is increased to 25 MPa and the temperature is increased to 45°C.

[0100] Comparative Example 7

[0101] This comparative example is the seventh embodiment of the present invention. Different from the first embodiment, in the S23 supercritical carbon dioxide drying process, the pressure of the drying kettle is increased to 13 MPa and the temperature is increased to 75°C.

[0102] Comparative Example 8

[0103] This comparative example is the eighth embodiment of the present invention. The difference from the first embodiment is that the modified semi-finished product obtained after the S22 hydrophobic modification process is not subjected to S23 supercritical drying. The specific drying process is as follows:

[0104] S22. The modified semi-finished product obtained after the hydrophobic modification process is placed in a muffle furnace and programmed to heat up to 200°C and dry for 2 hours, and finally cooled to room temperature to obtain SiO2 aerogel.

[0105] Performance testing:

[0106] The preparation cost of SiO2 aerogel, the specific preparation cost reduction rate calculation method is shown in the following formula:

[0107] SiO2 aerogel preparation cost reduction rate = 40% × [NN × (1-M%) - 1 / 5N × M%] / N

[0108] In the formula: the price of organic silicone ester is N, the price of silica sol is 1 / 5N, and the substitution ratio is M%.

[0109] The present invention uses silica sol to replace 20wt% to 40wt% of organic silicone grease. The cost of silica sol is about 1 / 5 of that of organic silicone ester, while organic silicone ester accounts for about 40% of the entire production cost. The SiO2 aerogel preparation process provided by the embodiment of the present invention can reduce the production cost by 6.6% to 12.1%. The cost reduction rate of SiO2 aerogel obtained in each embodiment and comparative example is shown in Table 1. It can be seen from Table 1 that, under the premise of ensuring the pore size, porosity and thermal insulation performance of SiO2 aerogel, the cost reduction rate of SiO2 aerogel obtained in the embodiment of the present invention is better than that of the comparative example. .

[0110] also, Figure 1 is a process flow chart of the present invention for preparing SiO2 aerogel, from Figure 1 It can be seen that alcohol participates in the system cycle during the preparation of SiO2 aerogel, and alcohol recycling is a conventional process. In the conventional preparation process in the prior art (without using silica sol), as the number of alcohol cycles increases, the impurity content becomes higher and higher, and the alcohol needs to be replaced every 3 to 6 months; and due to the high impurity content of alcohol, a distillation tower is required to recover the alcohol. However, the present invention adds silica sol as a silicon source on the basis of organic silicone ester. Since the silica particles of silica sol act as "seeds" to accelerate the condensation of monomers, reduce the residual organic monomers in alcohol, and contribute to the stability of the recycled alcohol. It only needs to use a simple evaporator for recovery, and the equipment investment and process costs are lower.

[0111] SiO2 aerogel yield: yield = (actual yield / theoretical yield × 100%); The theoretical yield can be calculated according to the reaction equation, and the actual yield can be measured to obtain the yield. The SiO2 aerogel yields obtained in the examples and comparative examples are shown in Table 1.

[0112] Purity of SiO2 aerogel: The main contents of SiO2 aerogel are silicon dioxide and residual organic matter. The organic matter is completely removed by heat treatment at 400℃ for 4h, and the purity of SiO2 aerogel of the product can be calculated according to the formula: (M2 / M1)*100%. Where M1 is the mass before heat treatment; M2 is the mass after heat treatment. The purity of SiO2 aerogel obtained in the embodiment and comparative example is shown in Table 1.

[0113] The yield and purity of SiO2 aerogel obtained in the examples and comparative examples are specifically shown in Table 1. The yield of SiO2 aerogel obtained in the examples is up to 99%, and the purity is up to 99.5%, which are better than the yield and purity of SiO2 aerogel obtained in the comparative examples.

[0114] It can be seen from Example 1 and Examples 4 to 7 that the selection of the mass ratio of organic silicone ester: silica sol: chelating agent will affect the yield and purity of SiO2 aerogel; it can be seen from Example 1 and Comparative Examples 4 and 5 that, when the mass ratio of organic silicone ester: silica sol: chelating agent is exceeded, the yield of the obtained SiO2 aerogel changes from 99% to 90%, and the purity changes from 99.5% to 96%, and both the yield and purity are reduced; it can be seen from Example 1 and Comparative Example 1 that when silica sol is not added, the yield of the obtained SiO2 aerogel changes from 99% to 82%, and the purity changes from 99.5% to 95%; it can be seen from Example 1 and Comparative Example 2 that when a chelating agent is not added, the yield of the obtained SiO2 aerogel changes from 99% to 83%, and the purity changes from 99.5% to 95.3%; the yield and purity of the obtained SiO2 aerogel are significantly reduced.

[0115] It can be seen from Example 1 and Examples 8 to 9 that the pH of the hydrolyzate A adjusted by S2 will affect the yield and purity of the SiO2 aerogel; it can be seen from Example 1 and Comparative Example 3 that when the pH of the hydrolyzate A is adjusted too high or too low, the yield of the obtained SiO2 aerogel changes from 99% to 88%, and the purity changes from 99.5% to 95.5%, and both the yield and purity are reduced.

[0116] It can be seen from Example 1 and Examples 10 to 12 that the choice of pressure in the S23 supercritical drying step will affect the yield and purity of SiO2 aerogel; it can be seen from Example 1 and Comparative Examples 6 and 7 that when the pressure is too large or too small, the yield of the obtained SiO2 aerogel changes from 99% to 95%, and the yield is reduced; it can be seen from Example 1 and Comparative Example 8 that when supercritical drying is not performed, the yield of the obtained SiO2 aerogel changes from 99% to 96%, and the yield is reduced.

[0117] Microstructure: (1) The microstructure of the SiO2 aerogel obtained in the example was observed using a scanning electron microscope. The SEM image of the SiO2 aerogel obtained in Example 1 is shown in Figure 2As can be seen from the figure, the prepared silica aerogel has significant pore characteristics and shows regular mesoporous morphological changes. The formed aerogel network skeleton is uniform and the pore size distribution is between 10-15nm. It is a typical mesoporous nanomaterial.

[0118] (2) Density test of SiO2 aerogel obtained in the embodiment and comparative example. The test method is: according to GB / T 34336 standard, use a thickness gauge to test the sample thickness, a steel ruler to test the length and width, and calculate the sample volume; use an electronic balance to test the sample mass; and calculate the sample density according to ρ=M / V. The test results of the density of SiO2 aerogel obtained in the embodiment and comparative example are shown in Table 1.

[0119] (3) The pore size and porosity of the SiO2 aerogel obtained in the embodiment and the comparative example were tested by using a Kanta surface area analyzer and a nitrogen adsorption-desorption method. The test results of the SiO2 aerogel structure obtained in the embodiment and the comparative example are shown in Tables 1 and Figure 3 . Figure 3 The figure is a BET nitrogen adsorption-desorption graph of SiO2 aerogel obtained in Example 1, with the abscissa being the pore size and the ordinate being the pore volume; it shows that the sample pore size is about 11.17nm and the pore volume is about 2.52cc / g. The porosity test method is: BET measures the adsorbent amount μ, and the porosity of the SiO2 aerogel obtained in the example and the comparative example is calculated by the formula porosity v=100%*(100-μ) / (100+μ).

[0120] The density, pore size and porosity of the SiO2 aerogel obtained in the examples and comparative examples are shown in Table 1. The density of the SiO2 aerogel obtained in the examples is as low as 180 Kg / m 3 The pore size is as small as 10-15nm and the porosity is as high as 98%, which is better than the density, pore size and porosity of the SiO2 aerogel obtained in the comparative example.

[0121] It can be seen from Example 1 and Examples 4 to 7 that the selection of the mass ratio of organosilicon ester: silica sol: chelating agent will affect the density, pore size and porosity of SiO2 aerogel; it can be seen from Example 1 and Comparative Examples 4 and 5 that when the mass ratio of organosilicon ester: silica sol: chelating agent is exceeded, the density of the obtained SiO2 aerogel increases from 180Kg / m 3 Change to 188Kg / m 3 The pore size changes from 10-15nm to 45-60nm, and the porosity changes from 98% to 96%. It can be seen from Example 1 and Comparative Example 1 that when no silica sol is added, the density of the obtained SiO2 aerogel changes from 180Kg / m 3 Change to 182Kg / m 3The pore size changes from 10-15nm to 40-80nm, and the porosity changes from 98% to 95%; it can be seen from Example 1 and Comparative Example 2 that when no chelating agent is added, the density of the obtained SiO2 aerogel changes from 180Kg / m 3 Change to 195Kg / m 3 The pore size changes from 10-15nm to 30-80nm, and the porosity changes from 98% to 93%. The density and pore size of the obtained SiO2 aerogel increase significantly while the porosity decreases.

[0122] It can be seen from Example 1 and Examples 8 to 9 that the pH of the hydrolyzate A adjusted by S2 will affect the density, pore size and porosity of the SiO2 aerogel; it can be seen from Example 1 and Comparative Example 3 that the pH of the hydrolyzate A is adjusted too high or too low, and the density of the obtained SiO2 aerogel increases from 180Kg / m 3 Change to 196Kg / m 3 The pore size changes from 10-15nm to 40-50nm, and the porosity changes from 98% to 95%. The density and pore size increase significantly while the porosity decreases.

[0123] It can be seen from Example 1 and Examples 10 to 12 that the selection of the pressure in the S23 supercritical drying step will affect the density, pore size and porosity of the SiO2 aerogel; it can be seen from Example 1 and Comparative Examples 6 and 7 that when the pressure is too large or too small, the density of the obtained SiO2 aerogel ranges from 180 Kg / m 3 Change to 187Kg / m 3 , the pore size changes from 10-15nm to 30-40nm, and the porosity changes from 98% to 97%; It can be seen from Example 1 and Comparative Example 8 that when supercritical drying is not performed, the density of the obtained SiO2 aerogel changes from 180Kg / m 3 Change to 226Kg / m 3 The pore size changes from 10-15nm to 50-100nm, and the porosity changes from 98% to 78%. The density and pore size of the obtained SiO2 aerogel increase significantly while the porosity decreases significantly.

[0124] Thermal insulation performance test: According to the national standard GB / T 10295 heat flow meter method, the thermal conductivity of the SiO2 aerogel obtained in Example 1 was tested using a German NETZSCH HFM446 Lambda M thermal conductivity meter. The specific results are shown in Figure 4 It can be seen from the figure that the thermal conductivity of the SiO2 aerogel obtained in Example 1 is 0.0157 W / (m·K). The test results of the thermal conductivity of the SiO2 aerogels obtained in the other examples and comparative examples are shown in Table 1.

[0125] It can be seen from Example 1 and Examples 4 to 7 that the selection of the mass ratio of organic silicone ester: silica sol: chelating agent will affect the thermal conductivity of SiO2 aerogel; it can be seen from Example 1 and Comparative Examples 4 and 5 that when the mass ratio of organic silicone ester: silica sol: chelating agent is exceeded, the thermal conductivity of the obtained SiO2 aerogel changes from 0.0157W / (m·K) to 0.0182W / (m·K); it can be seen from Example 1 and Comparative Example 1 that when silica sol is not added, the thermal conductivity of the obtained SiO2 aerogel changes from 0.0157W / (m·K) to 0.0186W / (m·K); it can be seen from Example 1 and Comparative Example 2 that when a chelating agent is not added, the thermal conductivity of the obtained SiO2 aerogel changes from 0.0157W / (m·K) to 0.0195W / (m·K), and the thermal conductivity of the obtained SiO2 aerogel increases rapidly.

[0126] It can be seen from Example 1 and Examples 8 to 9 that the pH of the hydrolyzate A adjusted by S2 will affect the thermal conductivity of the SiO2 aerogel; it can be seen from Example 1 and Comparative Example 3 that when the pH of the hydrolyzate A is adjusted to be too high or too low, the cost of the obtained SiO2 aerogel changes from 0.0157 W / (m·K) to 0.0177 W / (m·K), and the thermal conductivity increases significantly.

[0127] It can be seen from Example 1 and Examples 10 to 12 that the choice of pressure in the S23 supercritical drying step will affect the thermal conductivity of the SiO2 aerogel; it can be seen from Example 1 and Comparative Examples 6 and 7 that when the pressure is too large or too small, the thermal conductivity of the obtained SiO2 aerogel changes from 0.0157W / (m·K) to 0.0172W / (m·K); it can be seen from Example 1 and Comparative Example 8 that when supercritical drying is not performed, the thermal conductivity of the obtained SiO2 aerogel changes from 0.0157W / (m·K) to 0.0236W / (m·K), and the thermal conductivity of the obtained SiO2 aerogel increases.

[0128] Hydrophobicity test: Place the SiO2 aerogel obtained in any embodiment or comparative example at an angle of 45° to the horizontal, with the center of the sample located at a given position below the nozzle. Spray the sample with a certain flow of water for a specified time, and then measure the change in the mass of the sample before and after spraying to calculate the volume percentage of the volume not occupied by water in the sample, which is the hydrophobicity. The hydrophobicity of the SiO2 aerogel obtained in the embodiment of the present invention is as high as 99.7%.

[0129] Table 1 Performance test of SiO2 aerogel in the examples and comparative examples

[0130]

[0131] In summary, the present invention provides a method for preparing SiO2 aerogel with low cost, and the obtained SiO2 aerogel has low density, small pore size, large porosity and good thermal insulation effect.

[0132] The above is only an implementation method of the invention, and does not limit the scope of patent protection. Those skilled in the art can make non-substantial changes or substitutions based on the invention, which still fall within the scope of patent protection.

Claims

1. A method for preparing SiO2 aerogel, comprising: S1. preparing hydrolyzate A; S2. Gelation of hydrolyzate A; It is characterized in that S1. Specifically: dissolve the organic silicon ester into a solution, adjust the pH of the solution to be acidic, then add a chelating agent and silica sol in sequence, and hydrolyze to obtain a hydrolyzate A.

2. The method for preparing SiO2 aerogel according to claim 2, characterized in that: The mass ratio of organic silicon ester: silica sol: chelating agent in S1 is (80-200): (10-30): (0.5-2).

3. The method for preparing SiO2 aerogel according to claim 2, characterized in that: The mass ratio of organic silicon ester: silica sol: chelating agent in S1 is (100-150): (15-25): (1-1.5).

4. The method for preparing SiO2 aerogel according to claim 1, characterized in that: In the above S1, the organosilicon ester is dissolved in alcohol to form a solution, and the pH value is adjusted to 2-4.

5. The method for preparing SiO2 aerogel according to claim 1, characterized in that: The specific steps of gelling the hydrolyzate A are as follows: adjusting the pH of the hydrolyzate A to be weakly alkaline to obtain sol B, and then subjecting the sol B to aging, hydrophobic modification and drying to obtain SiO2 aerogel.

6. The method for preparing SiO2 aerogel according to claim 2, characterized in that: The pH of the hydrolyzate A in the gelling step S2 is 7-8.

7. The method for preparing SiO2 aerogel according to claim 1, characterized in that: The content of silicon dioxide in the S1 silica sol is ≥30wt%.

8. The method for preparing SiO2 aerogel according to claim 5, characterized in that: The hydrophobic modification process in S2 is to immerse the wet gel in a modifying liquid; the wet gel is obtained by aging sol B; the volume ratio of the wet gel to the modifying liquid is 1:(1-1.5); the modifying liquid is composed of a modifier and an alcohol, wherein the content of the modifier is (3-15) wt%.

9. The method for preparing SiO2 aerogel according to claim 2, characterized in that: The drying process in S2 is supercritical carbon dioxide drying; the pressure in the supercritical drying process is 16-20 MPa and the temperature is 50-70°C.

10. Use of SiO2 aerogel prepared by the method for preparing SiO2 aerogel according to any one of claims 1 to 9 in preparing thermal insulation materials.

Citation Information

Patent Citations

  • Method for preparing low density silica aerogel under normal pressure

    CN103435055A